2017
DOI: 10.1111/1911-3846.12313
|View full text |Cite
|
Sign up to set email alerts
|

Board Gender Diversity, Auditor Fees, and Auditor Choice

Abstract: We examine whether the presence of female directors and female audit committee members affect audit quality in terms of audit effort and auditor choice by using observations from a sample of U.S. firms, spanning the years 2001-2011. We find, after controlling for endogeneity and other board, firm, and industry characteristics, that firms with gender-diverse boards (audit committees) pay 6 percent (8 percent) higher audit fees and are 6 percent (7 percent) more likely to choose specialist auditors compared to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
245
9
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 192 publications
(282 citation statements)
references
References 70 publications
23
245
9
5
Order By: Relevance
“…Very little research has been done on the impact of independence, financial expertise, and the interlocking of audit committee members on the appointment of high‐quality auditors. Our review has also found that certain demographic variables of corporate directors, examined from the perspectives of nonaccounting disciplines, have been introduced into the auditor choice literature (Cheng & Leung, ; Lai et al, ). Future research taking such new directions, while linking corporate boards and audit committees to auditor appointment directly, will certainly enrich our understanding of the incentives and motivations for auditor choice.…”
Section: Implications Future Research and Concluding Remarksmentioning
confidence: 93%
See 3 more Smart Citations
“…Very little research has been done on the impact of independence, financial expertise, and the interlocking of audit committee members on the appointment of high‐quality auditors. Our review has also found that certain demographic variables of corporate directors, examined from the perspectives of nonaccounting disciplines, have been introduced into the auditor choice literature (Cheng & Leung, ; Lai et al, ). Future research taking such new directions, while linking corporate boards and audit committees to auditor appointment directly, will certainly enrich our understanding of the incentives and motivations for auditor choice.…”
Section: Implications Future Research and Concluding Remarksmentioning
confidence: 93%
“…Jiraporn et al () further suggested that the independent boards adopted as a result of the passage of SOX (US House of Representatives, ) are utilized by firms as a substitute for a Big N auditor. Lai, Srinidhi, Gul, and Tsui () documented a positive association between gender‐diverse boards (presence of at least one female director on the board and audit committee) and the appointment of industry‐specialist auditors . Davison et al () concluded that there was a strong link between companies audited by the same public accounting firm and those having common directors in Australia.…”
Section: Determinants Of Auditor Choicementioning
confidence: 99%
See 2 more Smart Citations
“…Control variables are determined based on findings of prior research on determinants of audit fees (e.g., Boo & Sharma, ; Goodwin‐Stewart & Kent, ; Hay et al, ; Huang, Masli, Meschke, & Guthrie, ; Lai, Srinidhi, Gul, & Tsui, ; Yang et al, ). The control variables used in Equation include Big 4 auditor ( B4 ), audit committee independence ( AC_IND ), audit committee financial expertise ( AC_EXP ), nonaudit fees ( LNONAF ), auditor tenure ( TENURE ), type of opinion ( OPINION ), inventory‐to‐total assets ratio ( INVTA ), receivables‐to‐total assets ratio ( RECTA ), number of subsidiaries ( SRSUB ), profitability ( ROA ), leverage ( LEV ), number of segments ( SEGMET ), firm size ( SIZE ), firm age ( AGE ) as a listed company, and year and industry controls.…”
Section: Methodsmentioning
confidence: 99%